Penerapan Moderasi Beragama melalui Pembelajaran Pendidikan Agama Islam di MTS. Muhammadiyah-13 Tanjung Morawa - Azra Henita Hanin Nasution; Hasrian Rudi Setiawan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to discover and confirm the role of PAI teachers in instilling the value of religious moderation in the school environment as an effort to prevent radicalism. The existence of radicalism can have a bad effect on students in the school environment. Apart from preparing the next generation, the rate of intolerance among students in schools is quite high. Schools are the main arena in strengthening the values ​​of religious moderation. One of the right steps to strengthen these values ​​is through Islamic Religious Education (PAI). This research method uses qualitative methods. Data collection techniques through interviews, observation and literature study. The research results revealed that Islamic Religious Education teachers at MTs. Muhammdiyah-13 Tanjung Morawa instills the values ​​of religious moderation through studying Islamic religion.